Mammary tubular carcinoma in a guinea pig (Cavia porcellus): case report - Oliveira, Radan Elvis Matias de; Oliveira, Rita de Kássia Matias de; Dalmagro, Mirian Juliana; Silva, Danby do Nascimento; Gurgel, João Vitor de Oliveira; Sousa, Ana Carolina Freitas Caetano de; Attademo, Fernanda Loffler Niemeyer; Soares, Maurílio Kennedy Feitosa; Arcoverde, Kathryn Nóbrega; Olinda, Robério Gomes; Santos, Paulo Ramos da Silva; Torres, Daniel César Barros; et al. (Brazilian Journal of Case Reports, 2023)
Mammary carcinomas are common malignant tumors encompassing the main diagnostic mammary gland tumor cause in female dogs and cats. Few reports in wild animals are, however, available. In this context, this study aimed to characterize the clinical and histological aspects of a mammary tubular carcinoma case in a guinea pig (Cavia porcellus). A four-year-old non-spayed female guinea pig was seen at a veterinary clinic in the municipality of Natal, Rio Grande do Norte, Brazil. Upon clinical examination, the animal was active, with a normal body condition, weighing 660 grams, hydrated, and presenting normal-colored mucous membranes. Increased left breast volume was observed, about 3.5 cm in diameter, non-adherent and with an ulcerated surface located medially to the mammary papilla, about 1.8 cm in diameter. The observed clinical findings indicated a presumptive neoplastic lesion diagnosis. A unilateral mastectomy was performed (left breast) and breast tissue fragments were histologically evaluated, confirming the tubular mammary carcinoma diagnosis. The surgical procedure and post-surgical treatment recommended in this report were proven efficient. Knowledge of diseases that affect non-conventional pets, such as the tubular mammary carcinoma reported herein, is paramount in improving the quality of life of these animals.